Association Between Cognitive Performance and Nutritional Status: Analysis From LASI-DAD - Manjusha Bhagwasia; Abhijith R. Rao; Joyita Banerjee; Swati Bajpai; Aruna V. Raman; Arunanshu Talukdar; Arvind Jain; Chhaya Rajguru; Lalit Sankhe; Debabrata Goswami; Ganapathy Sankaralingam Shanthi; Govind Kumar; et al. (Gerontology and Geriatric Medicine, 2023)
Malnutrition in low- and middle-income countries causes cognitive decline and other health problems. Harmonized Diagnostic Assessment of Dementia for Longitudinal Aging Study in India (LASI DAD) is an extensive study on late-life cognition and dementia. This study examines the link between nutrition and cognitive abilities in older adults using data from the LASI DAD. We conducted descriptive statistics on nutritional parameters (body-mass index, waist-hip ratio, and Mini-Nutritional Assessment), cognitive functions, and socio-demographic variables in 2,892 adults aged ≥60 years. Cognitive domains assessed included delayed recall, orientation, language, executive function, abstract reasoning, and attention. Cognitive impairment was defined as impaired performance in two or more domains. Mean age was 69.3 ± 7.1 years, 52.9% were female, and 57.5% were illiterate. Low body-mass index (adjusted OR: 1.88, p  < .001), at risk of malnutrition (adjusted OR: 1.89, p  < .001) and malnourished (adjusted OR: 2.86, p  < .001) on Mini-Nutritional Assessment were associated with the presence of cognitive impairment. Better cognitive performance was associated with increased body mass index (adjusted OR: 0.74, p -.03), hemoglobin (adjusted OR: 0.91, p -.006), and serum albumin (adjusted OR: 0.38, p  < .001). This study shows that nutritional status assessed by anthropometric measures and blood markers is strongly linked to cognitive performance in older adults.